255. CURRENT STATUS IN POSTOPERATIVE SHORT-TERM OUTCOMES OF ESOPHAGEAL RECONSTRUCTION USING THE GASTRIC TUBE AND FREE JEJUNUM FOR CERVICAL ESOPHAGEAL CANCER. (24th September 2022) - Miyawaki, Yutaka; Tachimori, Hisateru; Nakajima, Yasuaki; Sato, Hiroshi; Miyata, Hiroaki; Sakuramoto, Shinichi; Shimada, Hideaki; Watanabe, Masayuki; Kakeji, Yoshihiro; Doki, Yuichiro; Kitagawa, Yuko
Abstract: Cervical esophageal cancer is rare of esophageal cancers. Therefore, there is currently no survey for a large cohort of postoperative short-term outcomes. The gastric tube or the free jejunum are the two major reconstructed organs in esophageal reconstruction after esophagectomy for cervical esophageal cancer. This study aimed to clarify the current status of esophageal reconstruction by reconstructed organ after esophagectomy for cervical esophageal cancer, especially postoperative morbidities and mortality. Based on the Japan National Clinical Database, 807 surgically treated cases of cervical esophageal cancer between January 1, 2016, and December 31, 2019, were enrolled. Clinical outcomes were compared between the gastric tube group and the free jejunum group. The frequency of surgical site infection in organ space, anastomotic leakage, pneumonia, empyema, and chylothorax was significantly higher in the gastric tube group (10.0%, 17.9%, 16.7%, 2.0%, and 3.3%, respectively) than in the free jejunum group (2.9%, 6.7%, 11.1%, 0.0%, and 0.3%, respectively) (p = <0.001, <0.001, 0.029, 0.008 and 0.005, respectively). Significantly more patients in the gastric tube group required long-term hospitalization over 90 days (p = 0.039). Although these two major reconstructed organs are often not oncologically selectable, our results suggested that the free jejunum reconstruction after esophagectomy for cervical esophageal cancer may be more desirable when confined resection of the cervical esophagus was oncologically acceptable.